2023
DOI: 10.1186/s12941-023-00561-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent bacteremia predicts poor outcomes among neutropenic patients with carbapenem-resistant gram-negative bloodstream infections receiving appropriate therapy

Abstract: Purpose Identifying persistent bacteremia early in patients with neutropenia may improve outcome. This study evaluated the role of follow-up blood cultures (FUBC) positivity in predicting outcomes among patients with neutropenia and carbapenem-resistant gram-negative bloodstream infections (CRGNBSI). Methods This retrospective cohort study conducted between December 2017 and April 2022 included patients more than 15 years old with neutropenia and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The Cox proportional hazard analysis using propensity score weighting revealed that FUCC positivity was not a predictor of mortality, which may be due to the insufficient sample size. However, the Kaplan-Meier analysis demonstrated that patients with persistent Gram-negative bacterial meningitis/encephalitis had a higher mortality rate than FUCC-negative patients, both in terms of infection-related death and all-cause mortality, consistent with previous research 21 on carbapenem-resistant Gram-negative bloodstream infections. The review 22 (Gatti et al, 2023) that collected data from a total of 11 observational studies reiterated similar conclusions.…”
supporting
confidence: 87%
“…The Cox proportional hazard analysis using propensity score weighting revealed that FUCC positivity was not a predictor of mortality, which may be due to the insufficient sample size. However, the Kaplan-Meier analysis demonstrated that patients with persistent Gram-negative bacterial meningitis/encephalitis had a higher mortality rate than FUCC-negative patients, both in terms of infection-related death and all-cause mortality, consistent with previous research 21 on carbapenem-resistant Gram-negative bloodstream infections. The review 22 (Gatti et al, 2023) that collected data from a total of 11 observational studies reiterated similar conclusions.…”
supporting
confidence: 87%